Switching to Another Oral Anticoagulant and Drug Discontinuation Among Elderly Patients With Nonvalvular Atrial Fibrillation Treated With Different Direct Oral Anticoagulants. (14th August 2019) - Baker, Christine L.; Dhamane, Amol D.; Rajpura, Jigar; Mardekian, Jack; Dina, Oluwaseyi; Russ, Cristina; Rosenblatt, Lisa; Lingohr-Smith, Melissa; Lin, Jay
We compared the risks of switching to another oral anticoagulant (OAC) and discontinuation of direct oral anticoagulants (DOACs) among elderly patients with nonvalvular atrial fibrillation (NVAF) who were prescribed rivaroxaban or dabigatran versus apixaban. Patients (≥65 years of age) with NVAF prescribed DOACs (January 1, 2013 to September 30, 2017) were identified from the Humana research database and grouped into DOAC cohorts. Cox regression analyses were used to evaluate whether the risk for switching to another OAC or discontinuing index DOACs differed among cohorts. Of the study population (N = 38 250), 55.9% were prescribed apixaban (mean age: 78.6 years; 49.8% female), 37.3% rivaroxaban (mean age: 77.4 years; 46.7% female), and 6.8% dabigatran (mean age: 77.0 years; 44.0% female). Compared to patients prescribed apixaban, patients prescribed rivaroxaban (hazard ratio [HR]: 2.08; 95% confidence interval [CI], 1.92-2.25; P < .001) or dabigatran (HR: 3.74; 95% CI, 3.35-4.18, P < .001) had a significantly higher risk of switching to another OAC during the follow-up; compared to patients prescribed apixaban, the risks of discontinuation were also higher for patients treated with rivaroxaban (HR: 1.10; 95% CI, 1.07-1.13, P < .001) or dabigatran (HR: 1.29; 95% CI, 1.23-1.35, P < .001).